Cloud Document Management System for PETRONAS Technical Standards - Azman, Alia’ (IRC, 2020)
Modernization has made the world more virtually accessible to information by the tip of our fingers. For my Final Year Project, I have come up with a project that brings benefit to my previous internship company which is with Engineering Excellence, Group Technical Solutions, PETRONAS and all of the focal persons of PETRONAS Technical Standards (PTS) especially PTS Secretariat. Previously, PTS Secretariat used Microsoft Excel as their platform to store all of the details for PTS. They also will create analysis every year and pasted it on Microsoft PowerPoint to present to the Head of GTS which is waste of time. A dashboard is a modern and well-designed Data Visualization and Business Intelligence tool that is used to track easily the analysis pattern of PTS throughout the years. With this dashboard, it is easier for them to track the analysis of PTS as well as the readership of the PTS documents.